Multi-Scale Mechanisms of Phaleria macrocarpa in Liver Fibrosis: From Hepatic Stellate Cell Reprogramming to Systems Pharmacology Insights - Fahrul Nurkolis (PT Dexa Medica, 2026)
Liver fibrosis represents a central pathological process that bridges chronic liver injury to cirrhosis and hepatocellular carcinoma, yet effective therapies across all etiologies remain limited. Phaleria macrocarpa (mahkota dewa), a traditionalIndonesian medicinal plant, has emerged as a promising candidate due to its rich phytochemical diversity and potential polypharmacological effects. This review aims to integrate current evidence at the molecular, cellular, and systems levels to elucidate the anti-fibrotic potential of P. macrocarpa, with particular focus on hepatic stellate cell (HSC) biology. We systematically synthesize findings from phytochemical profiling, in vivo fibrosis models, early clinical observations, and recent systemic pharmacology studies, including data on standardized fractions such as Proliverenol. Available evidence consistently demonstrates that P. macrocarpa attenuates key drivers of fibrosis, including oxidative stress, inflammatory signaling (e.g., NF-κB/TNF-α), and pro-fibrogenic mediators such as TGF-β1, thereby reducing fibrotic burden in experimental models. At the compound level, constituents such as gallic acid and mangiferin provide proof-of-principlefor direct modulation of HSC activation and fibrogenesis-related pathways. However, a critical mechanistic gap remains: current studies primarily support suppression of the fibrogenic microenvironment rather than direct reprogramming of HSCs toward quiescence, apoptosis, or senescence. Recent network pharmacology analyses highlight key regulatoryhubs (e.g., RELA, PTGS2, SIRT1, GSK3B), suggesting that P. macrocarpa operates through multi-target mechanisms intersecting inflammatory, metabolic, and survival pathways. We propose a multi-scale framework that positions P. macrocarpa as a systems-pharmacology-driven anti-fibrotic candidate and emphasize the need for future studies targeting HSC-specific phenotypes, integrating single-cell omics, and providing translational validation. Advancing this plant froma hepatoprotective agent to a fibrosis-focused therapeutic will require direct mechanistic interrogation of stellate cell state transitions and rigorous clinical evaluation.